[commit: ghc] D5439: Use unicode arrows with -fprint-unicode-syntax (ac7d79c)

git at git.haskell.org git at git.haskell.org
Thu Dec 27 16:59:15 UTC 2018


Repository : ssh://git@git.haskell.org/ghc

On branch  : D5439
Link       : http://ghc.haskell.org/trac/ghc/changeset/ac7d79c1552eb10e90ec1d4866d843b822aadc5d/ghc

>---------------------------------------------------------------

commit ac7d79c1552eb10e90ec1d4866d843b822aadc5d
Author: Krzysztof Gogolewski <krz.gogolewski at gmail.com>
Date:   Tue Dec 18 00:14:16 2018 -0500

    Use unicode arrows with -fprint-unicode-syntax
    
    See #8959, this is one more place where we
    can pretty-print Unicode syntax.
    
    Test Plan: validate
    
    Reviewers: nomeata, bgamari
    
    Reviewed By: bgamari
    
    Subscribers: rwbarton, carter
    
    GHC Trac Issues: #8959
    
    Differential Revision: https://phabricator.haskell.org/D5439


>---------------------------------------------------------------

ac7d79c1552eb10e90ec1d4866d843b822aadc5d
 compiler/hsSyn/HsTypes.hs                  | 2 +-
 testsuite/tests/ghci/scripts/T8959b.stderr | 4 ++--
 2 files changed, 3 insertions(+), 3 deletions(-)

diff --git a/compiler/hsSyn/HsTypes.hs b/compiler/hsSyn/HsTypes.hs
index 993b020..4ab15b2 100644
--- a/compiler/hsSyn/HsTypes.hs
+++ b/compiler/hsSyn/HsTypes.hs
@@ -1444,7 +1444,7 @@ ppr_fun_ty ty1 ty2
   = let p1 = ppr_mono_lty ty1
         p2 = ppr_mono_lty ty2
     in
-    sep [p1, text "->" <+> p2]
+    sep [p1, arrow <+> p2]
 
 --------------------------
 ppr_tylit :: HsTyLit -> SDoc
diff --git a/testsuite/tests/ghci/scripts/T8959b.stderr b/testsuite/tests/ghci/scripts/T8959b.stderr
index 28b48fd..a814d2e 100644
--- a/testsuite/tests/ghci/scripts/T8959b.stderr
+++ b/testsuite/tests/ghci/scripts/T8959b.stderr
@@ -12,5 +12,5 @@ T8959b.hs:8:7: error:
 T8959b.hs:10:7: error:
     • Couldn't match expected type ‘(∀ a2. a2 → a2) → a1’
                   with actual type ‘()’
-    • In the expression: () ∷ (∀ a. a -> a) -> a
-      In an equation for ‘baz’: baz = () ∷ (∀ a. a -> a) -> a
+    • In the expression: () ∷ (∀ a. a → a) → a
+      In an equation for ‘baz’: baz = () ∷ (∀ a. a → a) → a



More information about the ghc-commits mailing list